2018
DOI: 10.1111/bph.14160
|View full text |Cite
|
Sign up to set email alerts
|

GPCRs in context: sexual dimorphism in the cardiovascular system

Abstract: This article is part of a themed section on Molecular Pharmacology of GPCRs. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.21/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 123 publications
(172 reference statements)
0
21
0
Order By: Relevance
“…Mice of both sexes were included in the study as it has been previously shown that deletion of Gpr37L1 has sexually dimorphic effects in mice ( Coleman et al, 2018 ). It is becoming increasingly obvious that males and females utilize different integrated physiological mechanisms to buffer and maintain cardiovascular homeostasis ( Hart et al, 2009 ; Mouat et al, 2018 ), thus it is important to investigate how mechanisms may differ between the sexes. The mechanism by which GPR37L1 effects change in the cardiovascular system is unclear, though we propose it interacts either directly or indirectly with central cardiovascular control regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice of both sexes were included in the study as it has been previously shown that deletion of Gpr37L1 has sexually dimorphic effects in mice ( Coleman et al, 2018 ). It is becoming increasingly obvious that males and females utilize different integrated physiological mechanisms to buffer and maintain cardiovascular homeostasis ( Hart et al, 2009 ; Mouat et al, 2018 ), thus it is important to investigate how mechanisms may differ between the sexes. The mechanism by which GPR37L1 effects change in the cardiovascular system is unclear, though we propose it interacts either directly or indirectly with central cardiovascular control regions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these effects in the brain, GPR37L1 has a reported role in maintaining blood pressure homeostasis ( Min et al, 2010 ; Coleman et al, 2018 ; Zheng et al, 2018 ), and may represent a potential drug target for the treatment of hypertension ( Smith, 2015 ). Supporting this, the closest non-orphan relative of GPR37L1 by phylogeny is the endothelin B receptor ( Valdenaire et al, 1998 ), which is known to have cardiovascular effects ( Mouat et al, 2018 ). In addition, GPR37L1 itself is encoded within a renin blood pressure quantitative trait locus, specifically in a sub-region that promotes high blood pressure in rats ( Flister et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to clarify if there exist hormone independent differences in immune cell GPER1 levels between males and females, or if sex-dependent differences in estrogen levels are critical, although both phenomena could be important in different clinical conditions. Sex related differences in the expression of several other GPCRs have already been described and have been related to sex dimorphism in cardiovascular diseases and stress responses ( 97 , 98 ).…”
Section: Future Perspectives In Gper1 Immunity-related Researchmentioning
confidence: 97%
“…Sexual differentiation starts during pre-natal life and continues throughout the life-span [69]. Relevantly, drug metabolism is influenced by sex–gender and age [70], as well as the activity of some inotropic and metabotropic receptors [71].…”
Section: Rulesmentioning
confidence: 99%